2005
DOI: 10.1300/j021v25n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Enticing Students to Careers in Gerontology

Abstract: Recognition of the increasing demand for gerontologically trained social work professionals prompted an investigation of the factors that attract undergraduate students to a career of working with older adults. Faculty (n = 10) and students (n = 10) from the disciplines of social work, nursing, consumer and family sciences, psychology, recreation, and business participated in focus groups addressing such topics as the inclusion of content on aging, influences on choice of major, perceptions of aging, and perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Nursing students' attitudes toward older adults have ranged from negative (Happell & Brooker, 2001) to neutral (de la Rue, 2003;Ryan & McCauley, 2004-2005. Students in other healthcare fields, such as social work, medicine, and dietetics, also reported negative attitudes toward aging (Anderson & Wiscott, 2003;Fitzgerald et al, 2003;Kaempfer, Wellman, & Himburg, 2002).…”
Section: Attitudes Toward Older Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nursing students' attitudes toward older adults have ranged from negative (Happell & Brooker, 2001) to neutral (de la Rue, 2003;Ryan & McCauley, 2004-2005. Students in other healthcare fields, such as social work, medicine, and dietetics, also reported negative attitudes toward aging (Anderson & Wiscott, 2003;Fitzgerald et al, 2003;Kaempfer, Wellman, & Himburg, 2002).…”
Section: Attitudes Toward Older Adultsmentioning
confidence: 99%
“…Research has shown that undergraduate students in nursing, social work, consumer and family sciences, psychology, dietetics, and medical school have limited knowledge of aging (Newell, Raji, Lieberman, & Beach, 2004;Rhee, Wellman, Castellanos, & Himburg, 2004;Ryan & McCauley, 2004-2005Wesley, 2005). Over 500 Australian undergraduate nursing students enrolled at nine different universities reported that they had little left to learn regarding gerontological nursing and expressed declining interest in caring for older adults at the end of their education (Happell, 2002).…”
Section: Knowledge Of Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But there must always be a method to our madness! Previous Gerontology & Geriatrics Education articles indicate the difficulty attracting students to our field (Wesley, 2005;Gross & Eshbaugh, 2011;Eshbaugh, Gross, Hillebrand, Davie, & Henninger, 2013), but also instruct us how to increase students' interest through education and exposure to older adults (Snyder, 2005;Hantman, Oz, Gutman, & Criden, 2013). Two articles within this edition of Gerontology & Geriatrics Education focus on service learning.…”
Section: From Pedagogy To Practice: Adventures In Student Engagementmentioning
confidence: 99%
“…adults among students (Lawrence et al, 2002;Lun, 2011;Wesley, 2005). Although the proposed causes vary, each has the potential to be addressed by a similar solution-improved public relations for aging, older adults, and the opportunities that surround them.…”
mentioning
confidence: 99%